Residue screening and analysis of enrofloxacin and its metabolites in real aquatic products based on ultrahigh-performance liquid chromatography coupled with high resolution mass spectrometry. (15th March 2023) - Dai, Jinxia; Wang, Ye; Lin, Hui; Sun, Yanmin; Pan, Yuning; Qiao, Jun-qin; Lian, Hong-zhen; Xu, Chun-xiang
Highlights: Deethylene-ENR was screened and detected in real fish samples for the first time. A new method for residue analysis of ENR and its metabolites in fish was developed. The detection rate of ENR metabolites in the analyzed crucian carp samples was high. Deethylene-ENR may be of concern as a possible risk candidate in aquatic products. Abstract: The abuse of enrofloxacin (ENR) in aquaculture and the lack of monitoring of other metabolites except ciprofloxacin (CIP) may lead to unknown harmful effects on human health. In this study, ENR metabolites were screened in real fish samples based on ultrahigh-performance liquid chromatography coupled with Q-Orbitrap mass spectrometry combined with Compound Discoverer software, and another metabolite deethylene-ENR besides CIP was detected and identified for the first time. Correspondingly, a method for the determination of ENR and CIP and the semi-quantitative analysis of deethylene-ENR in aquatic products was established. Method validation illustrated that excellent linearity and satisfactory recoveries of analytes were obtained. Limits of detection of ENR and CIP were both 0.1 μg kg −1, and their limits of quantification both 1 μg kg −1 . CIP and deethylene-ENR were detected in 12 of 14 ENR-positive fish samples, so deethylene-ENR should be of concern as a possible risk candidate in aquatic products.